A proposed solution to the species problem in velvet worm conservation (Onychophora) (UNED Research Journal, 2018)
Onychophorans or velvet worm are the only phylum without extant marine species and the only invertebrates with a true placenta, but most species are rare and thus more likely to become extinct. A key obstacle for their conservation is the time and work needed to describe species with the high standards current taxonomy, and many species will remain undescribed and without any name for years. Here we propose a way to associate information with undescribed species: "common names", a solution that has proved its value in ornithology. Onychophoran common names must include a geographic indicator and a description a salient characteristic, and to show its viability, here we apply our proposal to the velvet worm fauna of southeastern Central America. Common names like "Lajas Ferruginous Brown Onychophoran", "Churuquita Collared Cinnamon Rufous Onychophoran" and "Antón Collared Mauve Onychophoran" will help conservation until formal Latin binomials become available.
Keywords: Conservation Onychophora; new solutions for threatened biodiversity; non-technical names for invertebrates; informal names; velvet worm common names